2016
DOI: 10.1021/acsami.5b10602
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lateral Size of Graphene Quantum Dots on Their Properties and Application

Abstract: Well-defined graphene quantum dots (GQDs) are crucial for their biological applications and the construction of nanoscaled optoelectronic and electronic devices. However, as-synthesized GQDs reported in many works assume a very wide lateral size distribution; thus, their apparent properties cannot truthfully reflect intrinsic properties of the well-defined GQDs, and more importantly, the applications of GQDs will be affected and limited as well. In this work, we demonstrated that different sized GQDs with a na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
81
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 106 publications
(87 citation statements)
references
References 46 publications
5
81
0
Order By: Relevance
“…Mu and co‐workers also discovered that cellular internalization of GO coated with protein was size dependent . Our previous work also showed that smaller sized GQDs exhibited weaker ability to quench the fluorescence of small molecules . These results highlighted the need for high‐quality GQDs with well‐defined properties to facilitate their biomedical applications and to understand their properties.…”
Section: Introductionmentioning
confidence: 66%
See 1 more Smart Citation
“…Mu and co‐workers also discovered that cellular internalization of GO coated with protein was size dependent . Our previous work also showed that smaller sized GQDs exhibited weaker ability to quench the fluorescence of small molecules . These results highlighted the need for high‐quality GQDs with well‐defined properties to facilitate their biomedical applications and to understand their properties.…”
Section: Introductionmentioning
confidence: 66%
“…However, aggregation between the reactants by the micelles was inevitable, which decreased the product yield. We recently discovered that gel electrophoresis was a very effective method that could be used to sort as‐prepared GQDs into different sizes, because the as‐prepared GQDs had peripheral carboxyl groups that were closely related to their sizes and charges . Three groups of differently sized GQDs with narrow size distributions could be obtained by gel electrophoresis, and each showed unique photoluminescence (PL) properties that were consistent with their sizes.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, cellular uptake efficiency of the counterpart material with a negative surface charge is strongly modulated by lateral size. [42] Likewise, Mei et al, reported this size-dependent photoluminescent phenomenon. [39] In this context, GO could be utilized as a nanocarrier platform for small-interfering RNA (siRNA) delivery with interest also for future theranostic applications.…”
Section: Lateral Sizementioning
confidence: 96%
“…[42] Moreover, bi/few-layers GO microsheets that underwent gradual deoxygenation, via thermal reduction, led to GO with different oxygenated functional groups corresponding to different photoluminescent peaks as follows; the yellow-red emission of the studied GO (maximum peak at ≈610 nm) was mainly associated with epoxy/hydroxyl groups, whereas the blue emission (maximum peak at ≈500 nm) was mainly ascribed to the observed carbonyl functional groups. More in-depth research is required since oxidation grade in addition to layer numbers and lateral size should be carefully and systematically controlled.…”
Section: Oxidation Degreementioning
confidence: 99%
See 1 more Smart Citation